Le ecopedagogie generatrici di nuove consuetudini: la prospettiva della pedagogia giuridica - Bellelli, Fernando (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The need to develop an integrated theory of human dignity, in which the one of performance and the one of endowment find adequate articulation, implies the affective turning point of the Philosophical-Theological, Human and Legal Sciences. In all this, the contribution of the compared reflection of the thought of Vico and Rosmini on the subjects is central to the juridical argument of custom. It is evident that juridical pedagogy is the specific pedagogical and legal discipline in which and by which it is possible to find the founding contribution to the ability of eco-pedagogy to generate new necessary habits for the transition from the Anthropocene to the Ecozoic Era